PERSEPSI GURU SMU TERHADAP PENILAIAN UNJUK KERJA PADA PEMBELAJARAN FISIKA KURIKULUM 2013 - Arjuna, Arjuna; Sitompul, Stepanus Sahala; Maria, Haratua Tiur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study is aimed to discribe the perception of high school teachers toward the authentic assessment of performance on physics learning using the 2013 curriculum in Singkawang. The type of research used is survey research. Subject in this study are physics teachers who teach class X 2013/2014 academic year in Singkawang. Data collection tool used in the form of a questionnaire. Of the seven  respondents who filled the quetionnaire obtained the percentage of teachers’ perceptions of the authentic assessment of performance of 86,81% includes in good qualitative criteria, where as many as 50,95% stated strongly agree,as many 45,24% stated agree, as much as 3,81% stated disagree, and as much as 0% stated strongly disagree. These findings are expected to provide an overview of teachers perceptions of the authentic assessment of performance in the 2013 curriculum physics learning at Singkawang.Keywords: Perception, assessment of performance, curriculum 2013